A LITERATURE REVIEW ON VARIOUS IRRIGATING MATERIALS USED IN ENDODONTICS PRACTICE - Dr Mitali Middha; Dr Rahul Sharma; Dr Harshita Wadhwa (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
The goal of root canal treatment either surgical or non-surgical is to remove all the vital & dead non vital tissues, microbes, and their toxic products from root canal system. Removal of irritants and prevention of recontamination of the root canal after treatment are the essential elements for successful outcomes. There are many irrigants that are used in the endodontic practice and in this article, we are trying to narrates the properties and requirements of the different irrigants.